FORMS OF POLITICAL PARTIES' PARTICIPATION IN ELECTION PROCESS IN THE RUSSIAN FEDERATION - M. Serbin (Russian Journal of Economics and Law)
The author views the main forms of political parties' participation in election process in the Russian Federation. Special attention is paid to such forms as candidate' registration, pre-election campaign, electors' funds formation, etc.